Application of low-cost natural zeolite catalyst to enhance monoaromatics yield in co-pyrolysis of wheat straw and waste tire. (December 2022) - Ahmed, Absar; Khan, Shoaib Raza; Zeeshan, Muhammad
Abstract: This study explored the impacts of low-cost natural zeolite (NZ) catalyst application on production of aromatic hydrocarbons during co-pyrolysis of wheat straw (WS) and waste tire (WT). Various blend ratios of WS and WT (1:0, 3:1, 1:1, 1:3 and 0:1) were investigated to determine the optimum ratio in the terms of oil quantity and quality. The blend ratio of WS:WT 1:3 was observed to be optimum combination with oil, char and gas yields of 45, 36 and 19 wt% respectively. The catalyst was found to have silicon to aluminum ratio (SAR), surface area and pore size of 7.39, 4.2 m 2 /g and 23.10 Å respectively. The incorporation of NZ catalyst into WS, WT and their blend ratio of 1:3 improved the quality of oil in the terms of hydrocarbons and physiochemical properties compared to their respective ratios in non-catalyst pyrolysis. The total hydrocarbons content was increased from 72.00 area% in case of non-catalytic pyrolysis of WS:WT (1:3) to 86 area% with addition of NZ while oxygenates were reduced from 20.20 to 10.50 area% respectively. The contents of desired aromatic hydrocarbons such as benzene, toluene and xylene (BTX) were increased to 61.0 area% in catalytic pyrolysis for WS:WT 1:3 compared to 45.59 area% in non-catalytic pyrolysis of the same combination. Moreover, the higher heating value (HHV) of 42.15 MJ/kg was observed in catalytic pyrolysis of WS:WT (1:3) compared to 40.70 MJ/kg in non-catalytic pyrolysis. Besides, Kinematic viscosity and density of the oil also improved with addition of catalyst. Highlights: Wheat straw (WS) derived oil has highest oxygenates and lowest hydrocarbons (HCs). HCs increased to 86 area% with NZ for optimum ratio of waste tire (WT):WS (1:3). Catalytic pyrolysis oil has 25% more BTX than that of co-pyrolysis at optimum ratio. Physicochemical properties of oil from catalytic pyrolysis were improved.